Radio‐Activated Selenium‐Doped Janus Ag/Ag2SexSy Nanoparticles for Precise Cancer NIR‐II Fluorescence Imaging and Radiosensitization Therapy - Kang Zhu; Zhanyuan Li; Jingjing Cao; Yixi Cao; Jimei Wang; Shiyu Wang; Ling Chen; Huiqin Zhou; Wei Huang; Hanxun Zou; Qunsheng Li; Jing Mu; et al. (Advanced Science)
Abstract The efficacy of radiotherapy (RT) is often limited by insufficient tumor selectivity and suboptimal therapeutic responses. To overcome these problems, a new kind of selenium‐doped Ag/Ag2S Janus nanoparticles (Ag/Ag2SexSy JNPs) is presented as radio‐responsive molecular probes for precise tumor imaging and enhanced radiosensitization. By adjusting the selenium precursor input, heterojunction nanoparticles with tunable doping ratios are synthesized, optimizing X‐ray absorption and energy storage properties. Upon X‐ray irradiation, the Ag/Ag2SexSy JNPs interact with overexpressed hydrogen peroxide (H2O2) in tumor cells, generating highly toxic hydroxyl radicals (·OH), which effectively induce tumor cell apoptosis. Additionally, Selenium incorporation improves electron–hole pair separation efficiency and enhances the photocurrent response, promoting increased electron transfer and ·OH generation, thus amplifying reactive oxygen species (ROS) production and enhancing radiosensitization. Furthermore, the fluorescence “OFF‐ON” mechanism, triggered by H2O2‐induced etching of silver allows real‐time monitoring of H2O2 levels via the second near‐infrared window (NIR‐II) fluorescence (FL) imaging “Turn On”, which delineates tumor boundaries for precise RT and reduce side effects to normal tissue. This dual‐functional platform not only enables real‐time tracking but also enhances therapeutic outcomes, offering a promising approach to precision cancer treatment.